Early prescription of direct oral anticoagulant for the treatment of intermediate-high risk pulmonary embolism: a multi-center, observational cohort study. Issue 196 (December 2020) - Chopard, Romain; Badoz, Marc; Eveno, Charly; Ecarnot, Fiona; Falvo, Nicolas; Kalbacher, Elsa; Capellier, Gilles; Guillon, Benoit; Schiele, François; Meneveau, Nicolas
Abstract: Objectives: The safety and efficacy of direct oral anticoagulants (DOACs) in intermediate-high risk pulmonary embolism (PE) are unknown. The aims of the present study were to describe outcomes of patients receiving early apixaban or rivaroxaban prescription rather than the recommended delayed prescription strategy. Methods: Retrospective post-hoc analysis based on prospectively collected data from a multicenter cohort including all consecutive PE patients stratified as intermediate-high risk. Group definitions were: early group with DOAC prescription <72 h after admission; delayed group with DOAC prescription between 72 h and discharge. The 30-day primary efficacy outcome was a clinical composite of all-cause death and hemodynamic decompensation. The 30-day primary safety outcome was major bleeding. Results: Among 2411 patients admitted with PE, 302 were treated with a DOAC for an intermediate-high risk PE: 34.2% in the early group and 65.9% in the delayed group. The primary outcome occurred in 4.8% (including 1 death and 4 hemodynamic decompensations) in the early DOAC group and in 9.0% in the delayed DOAC group (OR, 0.44, 95% CI 0.15–1.30). The rate of major bleeding did not differ between groups (OR, 0.99; 95% CI 0.45–2.18). The length of stay was numerically shorter in the early group whereas the other outcomes did not differ significantly. Conclusion: The rate of 30-day outcomes was low in patients receiving a DOAC earlier after admission. Patients in the early DOAC group had a numerically shorter length of stay, with similarly low rates of death and bleeding, and similar RV function recovery compared to the delayed strategy. Graphical abstract: Unlabelled Image Highlights: One third of intermediate-high risk PE patients treated with DOAC receive them early The rate of outcomes in patient receiving a DOAC early after admission was low. Early DOAC pts were discharged earlier. Adverse outcome rates were similar between groups.